Enhancing organizational performance through agility strategies: The mediating effects of green innovation and digital transformation - Yusup, Yusup; Subyantoro, Arief; HC, R Heru Kristanto (Asian Management and Business Review, 2025)
Amid disruption and constant change, the ability to respond with flexibility, often referred to as strategic agility, has become vital in helping MSMEs remain competitive. This is especially true for the handicraft sector, which continues to feel the effects of the pandemic alongside increasing pressure to adopt digital and sustainable practices. This research explores how strategic agility directly influences organizational performance, while also examining whether digital transformation and green innovation play mediating roles in that relationship. The study builds upon the resource-based view (RBV) and natural-resource-based view (NRBV), which underline the importance of internal strengths and sustainable approaches as key drivers of advantage. Data were gathered from 50 MSMEs in the Special Region of Yogyakarta through a Likert-scale questionnaire. The analysis was conducted using partial least squares structural equation modeling (PLS-SEM). Results indicate that strategic agility contributes positively to performance, both on its own and by facilitating green innovation and digital transformation. Moreover, the presence of green innovation appears to reinforce the effect of digital transformation on business outcomes, emphasizing the value of environmentally responsible practices. This research enriches current literature by presenting an integrated framework and offering insights that can assist MSMEs in aligning their innovation strategies with both technological and ecological shifts. In conclusion, strengthening strategic agility along with developing digital capacity and sustainability focus can be a valuable direction for MSMEs. The findings offer useful input for practitioners and policymakers seeking to formulate long-term, resource-based strategies for business resilience in evolving markets.